10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background Children with cerebral palsy (CP) are at increased risk of malnutrition due to feeding difficulties, higher nutritional requirements and the additional caregiving demands associated with disability. Households caring for children with CP may therefore experience greater vulnerability to food insecurity, particularly in low-resource contexts. This study explored how children with CP experience feeding and nutrition within the South African food environment. Methods An explanatory mixed-methods pilot study was conducted with primary caregivers of children aged 2-8 years with CP in South Africa. Caregivers completed a descriptive survey assessing household food access, feeding practices and child functional severity using the Gross Motor Function Classification System (GMFCS) and Eating and Drinking Ability Classification System (EDACS). Semi-structured interviews were subsequently conducted to explore feeding experiences. Data were interpreted using the food security framework. Results Although food was generally present within households, caregivers reported limited access to foods that met the nutritional and feeding needs of children with CP. Feeding required extensive caregiver adaptations, including texture modification and prolonged mealtimes. Economic constraints, reliance on social grants, transport barriers and unstable income further affected household food access and stability. Children with greater feeding impairment experienced more pronounced challenges in achieving safe and nutritionally adequate diets. Conclusions Children with CP experience intersecting vulnerabilities across the dimensions of food availability, access, utilization and stability. Disability-responsive nutrition policies, strengthened caregiver support and integrated health and social protection strategies are needed to support equitable access to adequate food for children with CP.